Patient Knowledge and Beliefs About Knee Osteoarthritis After Anterior Cruciate Ligament Injury and Reconstruction. Issue 8 (August 2016) - Bennell, Kim L.; van Ginckel, Ans; Kean, Crystal O.; Nelligan, Rachel K.; French, Simon D.; Stokes, Maria; Pietrosimone, Brian; Blackburn, Troy; Batt, Mark; Hunter, David J.; Spiers, Libby; Hinman, Rana S.
Abstract : Objective: To explore patients' knowledge and beliefs about osteoarthritis (OA) and OA risk following anterior cruciate ligament (ACL) injury, to explore the extent to which information about these risks is provided by health professionals, and to examine associations among participant characteristics, knowledge, and risk beliefs and health professional advice. Methods: A custom‐designed survey was conducted in Australian and American adults who sustained an ACL injury, with or without reconstruction, 1–5 years prior. The survey comprised 3 sections: participant characteristics, knowledge about OA and OA risk, and health professional advice. Results: Complete data sets from 233 eligible respondents were analyzed. Most (70%, n = 164) rated themselves as being at greater risk of OA than their healthy peers, although only 56% (n = 130) were able to identify the correct OA definition. While most agreed that ACL (73%, n = 168) and/or meniscal injuries (n = 181, 78%) increase the risk of OA, 65% (n = 152) believed that ACL reconstruction reduced the risk of OA, or they did not know. A total of 27% (n = 62) recalled discussing their OA risk with a health professional. Participants who were female, younger, or had a lower body mass index or higher physical activity level were more likely to recognize meniscal tears and meniscectomy as risk factors of OA. A history of professional advice was associated with beliefs about increased OA risks. Conclusion: Patients sustaining an ACL injury require better education from health professionals about OA as a disease entity and their elevated risk of OA, irrespective of whether or not they undergo surgical reconstruction.